Livestock production systems, subsidies and its implications: An investigation through review of literature - Chandel, B S; Lal, Priyanka; Kumari, Binita (Indian Journal of Dairy Science, 2019)
In the process of development, among different agricultural subsectors, livestock is one of the fastest growing sectors, and this subsector has been provided various incentives in the form of subsidy and support. This paper summarizes the findings of the past studies on livestock production systems, subsidies and its implications which were constrained by the limited literature available covering all the aspects. In livestock sector, subsidies have been provided on investment, purchase of animals, feed and insurance. There is no doubt that subsidies have well served its short term objectives, nevertheless, it has had adverse effects on environment and economic efficiency in the long run such as over-exploitation of fish stock, grazing lands and soil degradation. Finally the paper comes out with information gaps on the topic that required to be addressed.Â